Penggunaan Media Benda Konkret Untuk Meningkatkan Kemampuan Berhitung Materi Perkalian Siswa Kelas 3 Sekolah Dasar - Arissona Dia Indah Sari; Za’iimah Putri Rahmadani (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2023)
To respond to the features and requirements of primary school kids who may lack fundamental numeracy abilities, learning material that reduces the dogma that mathematics is difficult and unpleasant is required. Basic education, where students may be actively involved in learning activities, requires the invention of tangible learning media (actual items) such as living things, solid objects, liquid objects, and so on. The goal of this study is to discover how physical items media might boost students' ability, passion, and activity in counting multiplication material in grade 3 primary school pupils. This study is a Class Action Research (CAR) at UPT SDN 49 GRESIK, which is located on Jl. Martapura I / 20 Gkb Sukomulyo, Sukomulyo, Kec. Manyar, Kab. Gresik, East Java, in the odd semester of the 2022/2023 school year, using students and instructors from class III B as subjects. The instruments consist of tests and observations, namely the multiplication problem test and the non-participant observation. (1) The learning outcomes of students after using tangible objects media demonstrate that the percentage of completion in cycle 1 is 52% and 82.60% in cycle II. (2) Student participation has raised the percentage of student involvement from 60% in cycle I meeting 1 and 67.5% in cycle II meeting 2 to 85% in cycle II meeting 1 and 95% in cycle II meeting 2. (3) Teacher activities have been effectively executed and have attained the stipulated percentage based on the results of the average percentage of teacher activities from cycle I meeting 1 of 62.5% and cycle I meeting 2 of 67.5% to cycle II meeting 1 of 87.5% and cycle II meeting 2 of 90%. As a consequence, the use of concrete object media to increase the capacity to count multiplication has been beneficial, yielding extremely good outcomes. Keywords: Concrete; counting; elementary; media; multiplication